Study on HarvestPlus' contribution to the development of national biofortification breeding programs - Douthwaite, Boru (International Food Policy Research Institute, 2021)
This evaluative review is one of a series of end-of-program studies being carried out by the CGIAR Research Program (CRP) on Agriculture for Nutrition and Health (A4NH) to document lessons from its achievements to inform future research and development (R&D) efforts. This study looks at lessons learned from HarvestPlus’ work with National Agricultural Research and Extension Systems (NARES) to develop and implement sustainable biofortification breeding programs. HarvestPlus is part of A4NH.